Altered molecular expression of TLR-signaling pathways affects the steady-state release of IL-12p70 and IFN-α in patients with relapsing-remitting multiple sclerosis. Issue 4 (May 2016) - Deckx, Nathalie; Willekens, Barbara; Wens, Inez; Eijnde, Bert O; Goossens, Herman; Van Damme, Pierre; Berneman, Zwi N; Cools, Nathalie
Recent evidence suggests a key role of dendritic cells (DC) in the immunopathogenesis of multiple sclerosis (MS). Whereas dysfunction of DC was reported in MS patients, the underlying cause for this is not fully elucidated yet. The aim of the present study was to compare the gene expression profile of molecules involved in TLR4 and TLR7 signaling in DC from patients with MS and healthy controls. For this, circulating DC subsets were purified from patients with relapsing-remitting MS (RRMS) and from healthy controls for quantitative real-time PCR analysis. Additionally, TLR responsiveness in peripheral blood was investigated. We observed an aberrant steady-state release of IL-12p70 and IFN-α in patients with RRMS compared with healthy controls. Expression of IRF1 and JUN was reduced in conventional DC from patients with RRMS. In plasmacytoid DC from patients with RRMS, expression of IRF7 and IFNGR1 was reduced, while higher expression levels of TLR4 and LY86 were found compared with DC from healthy controls. The observed alterations in the gene expression of molecules involved in the TLR4 and TLR7 signaling pathways in circulating DC subsets may underlie the impaired IL-12p70 and IFN-α secretion in patients with RRMS, thereby potentially contributing to the disease pathogenesis of MS.